Tensions of empire : colonial cultures in a bourgeois world - Cooper, Frederick, 1947-; Stoler, Ann Laura (Berkeley, Calif. : University of California Press, 1997)
Starting with the premise that Europe was made by its imperial projects as much as colonial encounters were shaped by events and conflicts in Europe, this volume investigates metropolitan-colonial relationships. It shows how "civilizing missions" often provided new sites for a bourgeois order.
Preface Acknowledgments Between Metropole and Colony: Rethinking a Research Agenda Ann Laura Stoler and Frederick Cooper Part I Framings 1 Liberal Strategies of Exclusion Uday S. Mehta 2 Imperialism and Motherhood Anna Davin 3 Of Mimicry and Man: The Ambivalence of Colonial Discourse Homi Bhabha Part II Making Boundaries Contents 4 Images of Empire, Contests of Conscience: Models of Colonial Domination in South Africa John L. Comaroff 5 Sexual Affronts and Racial Frontiers: European Identities and the Cultural Politics of Exclusion in Colonial Southeast Asia Ann Laura Stoler 6 "The Conversion of Englishmen and the Conversion of the World Inseparable": Missionary Imperialism and the Language of Class in Early Industrial Britain Susan Thorne 7 Race, Gender, and Citizenship in the German Colonial Empire Lora Wildenthal Part III Colonial Projects 8 "Le bebe en brousse": European Women, African Birth Spacing, and Colonial Intervention in Breast Feeding in the Belgian Congo Nancy Rose Hunt 9 Tradition in the Service of Modernity: Architecture and Urbanism in French Colonial Policy, 190G-1930 Gwendolyn Wright 10 Educating Conformity in French Colonial Algeria Fanny Colonna Part IV Contesting the Categories of Rule 11 The Difference-Deferral of a Colonial Modernity: Public Debates on Domesticity in British Bengal Dipesh Chakrabarty 12 The Dialectics of Decolonization: Nationalism and Labor Movements in Postwar French Africa Frederick Cooper 13 Cars Out of Place: Vampires, Technology, and Labor in East and Central Africa Luise White Notes on Contributors Index
Includes bibliographical references and index.
Keywords: History, Modern -- 19th century; History, Modern -- 20th century; Imperialism -- History -- 19th century; Imperialism -- History -- 20th century; Colonies; Europe -- History -- 1789-1900.; Europe -- History -- 20th century